Clumsy Packing of Polyominoes in Finite Space - Miller, Emma; O'Connor, Mitchel; Shank, Nathan (The PUMP Journal of Undergraduate Research, 2024)
Clumsy packing is considered an inefficient packing, meaning we find the minimum number of objects we can pack into a space so that we can not pack any more object. Thus, we are effectively spacing the objects as far apart as possible so that we cannot fit another object. In this paper, we consider the clumsy packing of polyominoes in a finite space, which must consider boundary conditions. We examine rectangle, L, T, and plus polyominoes of various sizes.